The Problem Of The Military Marches Of The Arabs To Ferghana In The Work Of Ibn A'sam Al-Kufi (Eurasian Journal of History, Geography and Economics, 2023)
Ibn, who is considered an important source in the study of the history of the conquest of Central Asia by the Arabs A'sam al-Kufi's work "Kitab al-futuh" is analyzed. The main attention is paid to the information about the history of Ferghana given in the source. In particular, the military campaigns of Qutayba ibn Muslim, Sa'id ibn 'Amr alHarashi, Muslim ibn Sa'id, and al-Ashras to the valley were researched based on comparative studies with other Arab sources